Bioengineering considerations in the prevention of medical device-related pressure ulcers. (July 2019) - Bader, D.L.; Worsley, P.R.; Gefen, A.
Abstract: Background: In recent years, it has become increasingly apparent that medical device-related pressure ulcers represent a significant burden to both patients and healthcare providers. Medical devices can cause damage in a variety of patients from neonates to community based adults. To date, devices have typically incorporated generic designs with stiff polymer materials, which impinge on vulnerable soft tissues. As a result, medical devices that interact with the skin and underlying soft tissues can cause significant deformations due to high interface pressures caused by strapping or body weight. Methods: This review provides a detailed analysis of the latest bioengineering tools to assess device related skin and soft tissue damage and future perspectives on the prevention of these chronic wounds. This includes measurement at the device-skin interface, imaging deformed tissues, and the early detection of damage through biochemical and biophysical marker detection. In addition, we assess the potential of computational modelling to provide a means for device design optimisation and material selection. Interpretation: Future collaboration between academics, industrialists and clinicians should provide the basis to improve medical device design and prevent the formation of these potentially life altering wounds. Ensuring clinicians report devices that cause pressure ulcers to regulatory agencies will provide the opportunity to identify and improve devices, which are not fit for purpose. Highlights: The formation of medical device-related pressure ulcers restricts effective management in a range of patients. Bioengineering technologies can assess the device-skin interface conditions. Biochemical and biophysical sensors can evaluate tissue status during device loading. Computational models verified with experimental data can inform the design of safer devices. Multidisciplinary collaboration is required to prevent these device related injuries.